2014
DOI: 10.3109/03014460.2014.916750
|View full text |Cite
|
Sign up to set email alerts
|

Association of neuropeptide Y gene rs16147 polymorphism with metabolic syndrome in patients with documented coronary artery disease

Abstract: The rs16147 polymorphism may be associated with presence of MetS among subjects with documented CAD. Carriage of NPY A allele in patients with CAD is associated with a higher prevalence of MetS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Some works [27] have shown a relationship of rs16147 with different cardiovascular risk factors, for example an increased risk of metabolic syndrome and its related phenotypes, such as central obesity and hyperglycemia, in obese subjects without the A allele. Another study [8] reported this relationship with metabolic syndrome in a non-Caucasian population. Insulin resistance is the main alteration in metabolic syndrome.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Some works [27] have shown a relationship of rs16147 with different cardiovascular risk factors, for example an increased risk of metabolic syndrome and its related phenotypes, such as central obesity and hyperglycemia, in obese subjects without the A allele. Another study [8] reported this relationship with metabolic syndrome in a non-Caucasian population. Insulin resistance is the main alteration in metabolic syndrome.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, the above-mentioned SNP has been shown to be related with serum levels of NPY [5] and to be responsible for more than half of the variation in the expression of NPY [6]. Few previous studies have shown an association between SNPs of NPY and early onset of atherosclerosis, stroke, and hypertension [7,8]. Moreover, adipose tissue is recognized as an endocrine organ producing several proteins, called adipokines, produced by adipose tissue (leptin, adiponectin, resistin, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the results in the literature are contradictory. Parizadeh et al [9] observed that GG homozygotes of rs14167 had a significantly decreased risk of MetS when compared with A allele carriers. The difference in design between this study and ours is important: firstly, the population of the previous study was not Caucasian and, secondly, all patients [9] had a severe complication of MetS as an inclusion criterion (i.e., documented coronary artery disease).…”
Section: Discussionmentioning
confidence: 99%
“…The association between NPY rs16147 SNP and MetS has not been studied extensively, and only 1 study in an Iranian population has been performed [9]. Given the limited information about the relationship of this SNP with MetS and adipokines in a Caucasian population, this study was designed with the aim to investigate the relationship of NPY rs16147 with body weight, insulin resistance, serum adipokine levels, and presence of MetS.…”
Section: Introductionmentioning
confidence: 99%
“…Although, in our previous study, we have reported that the NPY rs16147 polymorphism may be associated with the presence of the metabolic syndrome among patients with documented CAD, and patients carrying the A allele are associated with a higher prevalence of the metabolic syndrome [28], the association between the NPY rs16147 SNP and CAD has not been extensively studied, and, to our knowledge, there is little information about the genetic susceptibility to CAD in the Iranian population. This cross-sectional study was designed to evaluate the potential association between the NPY rs16147 polymorphism and the risk of CAD in an Iranian population.…”
Section: Introductionmentioning
confidence: 99%